Developing worksheet-based 7E learning cycle to foster elementary school students’ critical and creative thinking skills - Perdana, Ryzal; Yanfika, Helvi; Sholehurrohman, Ridho; Bertiliya, Winda Annisha (Journal of Educational Management and Instruction (JEMIN), 2024)
Enhancing students' critical and creative thinking skills is a crucial objective in education. Numerous studies have explored effective teaching methods to foster these skills, with models such as Problem-Based Learning (PBL), the STEM-5E Learning Cycle, and the 7E Learning Cycle showing significant promise. This study aims to develop and validate a worksheet designed to enhance critical and creative thinking in elementary school students using the 7E Learning Cycle, following the ADDIE instructional design model. The study was conducted with fourth-grade students at SDN 1 Pasir Gintung, Lampung province of Indonesia, with two classes serving as the sample: Class IV A as the experimental group and Class IV B as the control group. Product validation indicated a high level of effectiveness, with a material average score of 0.833, a language component score of 0.693, and a media aspect score of 0.917. The test tool, validated as part of the research product, achieved an average score of 0.733. Instructor feedback was overwhelmingly positive, with a 98% approval rate, while student feedback indicated a 94% satisfaction rate, both underscoring the product's practical value. Post-test results from the experimental group demonstrated a significant improvement in critical and creative thinking skills, with an average score of 89.49, markedly higher than the control group. These findings provide empirical evidence supporting the effectiveness of the 7E Learning Cycle in enhancing critical and creative thinking through the use of the developed worksheet in educational settings.